Peran Strategis Teknologi Informasi dan Komunikasi di STIT Al-Ittihadiyah Labuhan Batu Utara - Mesiono Mesiono; Handoko Handoko; Abdul Hakim Siregar; Hamdan Hamdan (Departement of Mathematics Education, 2023)
Higher education such as universities, colleges and other high schools education management is applied differently from secondary or primary education institutions because it is more complex. Educational institutions must carry out educational programs as well as possible so that the quality of education is increasingly advanced. In order to carry out education as well as possible, it is necessary to have good management or institutional management. The development of information and communication technology has given many roles in the world of education. Not only applied in direct learning, but in the implementation of management of educational institutions is also needed so that it can support the course of learning and lectures. Many universities have used information technology to support their activities. In general, computer technology is used to support administrative processes, such as academic administration, finance, and personnel. The emergence of problems like the one above and the way universities deal with them shows that universities still view the implementation of information technology as something that is